Arch of Triumph from Court of Flowers, San Francisco Exposition (H.S. Crocker Co., Inc.)
The Tower of the Sun, central spire of the Golden Gate International Exposition, is approached from the Temple Compound through the Courts of Flowers and Reflections. Here is it seen towering above the Arch of Triumph.